Is helping always the preferred decision? Preschool- and elementary school-aged children's helping decisions in complex social situations - Schuhmacher, Nils; Rack, Natalie; Beckmann, Lena; Kärtner, Joscha (Frontiers in Developmental Psychology, 2023)
In the present study we investigated 4-to 8-year-olds' moral decisions in complex social situations (N = 152 children; 69 girls; all European, urban, and middle-class). In a 2 x 2 design, each child was asked whether a story protagonist should help or not help in four different conditions, namely helping a friend or stranger get their own object, or helping a friend or stranger take someone else's object. We found that children clearly approve of helping in moral conditions and generally disapprove of helping in situations involving immoral outcomes. We also found that older children were more likely to disapprove of helping in immoral contexts. Moreover, children preferred helping friends to helping strangers only in moral but not in the immoral conditions. In summary, these findings propose that children undergo meaningful changes in their helping decisions from preschool to elementary school years.